Managing Global Supply Chains: Compliance, Security, and Dealing with Terrorism - Cook, Thomas (CRC Press, 2009)
September 11, 2001 had a profound impact upon individuals, institutions, and governments, but also upon the world of global trade. Years later, the reverberations of this deliberate and focused act of terrorism are manifest in much more stringent logistics, documentary requirements, and regulations. A single source on compliance and security, written from a supply chain manager’s perspective, Managing Global Supply Chains sorts out all the issues and frames a comprehensive strategy for supply chain executives in the post 9/11 world.